Large area magnetic micropallet arrays for cell colony sorting. Issue 1 (25th November 2015) - Cox-Muranami, Wesley A.; Nelson, Edward L.; Li, G. P.; Bachman, Mark
Abstract : Large area magnetic micropallets with ferromagnetic cores were fabricated on translucent gold thin films enabling consistent laser release of individual cell colonies via vapor bubble formation beneath the pallets. Abstract : A new micropallet array platform for adherent cell colony sorting has been developed. The platform consisted of thousands of square plastic pallets, 270 μm by 270 μm on each side, large enough to hold a single colony of cells. Each pallet included a magnetic core, allowing them to be collected with a magnet after being released using a microscope mounted laser system. The micropallets were patterned from 1002F epoxy resist and were fabricated on translucent, gold coated microscope slides. The gold layer was used as seed for electroplating the ferromagnetic cores within every individual pallet. The gold layer also facilitated the release of each micropallet during laser release. This array allows for individual observation, sorting and collection of isolated cell colonies for biological cell colony research. In addition to consistent release and recovery of individual colonies, we demonstrated stable biocompatibility and minimal loss in imaging quality compared to previously developed micropallet arrays.